Hepatitis E virus infection in HIV positive ART naïve and experience individuals in Nigiera (2013)
" Background: Studies have shown Hepatitis E Virus to be a causative agent of acute and chronic hepatitis in severely immunocompromised patients such as organ transplant recipients and person with HIV infection. This study was designed to determine the burden of HEV infection among HIV positive individuals in Nigeria and the effect of HIV treatment on the burden of HEV infection among this group of patients. Methods: Aliquot of plasma samples collected for laboratory investigations such as CD4 enumeration, blood chemistry (AST, ALT, Creatine, Urea) were used to determine the presence of HEV IgG and IgM antibodies using commercially available ELISA. Samples analysed in the study were collected from 180 HIV positive individuals (90 ART naive and 90 ART experienced) attending the ART clinic at the University College Hospital, Ibadan, Nigeria. Results: Twenty two of the 180 (12.2%) samples were positive for either HEV IgG (20/180) or IgM (2/180). The rate of HEV IgG was higher among ART naive individuals and the two IgM positive persons were ART naive. There was no significant difference in the mean CD4 count and mean ALT between HEV seronegative and seropositive individuals (P = 0.8 and 0.2 respectively). Conclusions: The results of this study suggest the need to test for HEV infection in HIV positive individuals for the early diagnosis and proper management since HEV is known to be fulminant in the presence of underlying liver disease that is common among HIV infected persons. In addition, the use of ART may reduce the incidence of HEV infection in HIV positive persons. "